PERAN STAKEHOLDERS DALAM PEMBERDAYAAN MASYARAKAT TERHADAP BUDIDAYA KAKAO (Studi di Kampung Klaisu Distrik Gresik Selatan Kabupaten Jayapura) - , Merlina Salomi Iryani Melmambessy, Purwanto, M.Phil ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to determine the role of stakeholders in the development community to empower cocoa farmers. This study implemented South Gresi District in Klaisu Village Jayapura Regency, during the study was conducted during the fourth lunar month, in March to June 2011. To answer the research objectives, the approach used to understand the phenomenon kualitaife, role of existing stakeholders. Informants selected sourced from four groups of stakeholders: community leaders, farmers' groups, governments and employers. Each group of informants selected a person, unless the agricultural office of Jayapura, taken as many as two informants. Data obtained, derived from primary and secondary data, then analyzed descriptive, to describe the role of each stakeholder, thus the data and information obtained is presented in the form of the statement quoted the informant. The results of the analysis show that the government is the most dominant interest groups in terms of business development roles cacao, it appears from the contribution of capital, means of agricultural production, especially cocoa and the provision of field agricultural extension workers (PPL) which provides information on cultivation techniques cocoa. PT. Sinar Mas Group, is the second dominant group stakeholer, after goverment important contribution of cocoa marketing. PT. Sinar Mas to buy dried beans from Klaisu villagers. While the contribution of community leaders in cocoa planting program shall be lower than the government and the private sector. Traditional leaders, such as ondofolo Ondoafi and has been instrumental in terms of customary land use permit under their control, while the religious leaders, was instrumental in gave the advice and motivation to the farmers and Ondoafi and ondofolo. Female characters, contribute to increasing knowledge through non-formal educational training in the form of processing cocoa beans into cocoa paste. Contribution of youth leaders in an effort to empower people klaisu, visible from the efforts of youth to form farmer groups based on clan, devoted to asset management and production facilities will be more effective and successful. From the revenue side, the program shows a significant success, there is increased revenue from the sale of cocoa. In terms of dependency, the program has yet to show success, because farmers still expect capital aid and equipment from the government through the offices of Jayapura Regency Estates.